PEMANFAATAN PENCAHAYAAN ALAMI PADA BANGUNAN KONDOMINIUM TRIBECA SOUTHERN UNIT 18 F PODOMORO CITY MEDAN - Jimmi Roy (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2022)
In architecture the use daylighting has always been an important part that is must beconsider in the design of buildings.One of the superblock developments in Medan is located on land developed by the developer Agung Podomoro Land. The superblock function is made with a condominium building as a multi-storey building on the floor consisting of several residential units, with each room unit having a complete living space, where the residents share the same facilities. Unit 18F Southern Tribeca condominium block Southern Tribeca. Lighting in the room in the condominium has an important meaning for residents to help each activity of the residents. In addition, space is also an important help in providing comfort for the wearer. Space users are faced with a great need for daylighting that is able to provide space comfort. This research discusses the installation of daylighting based on daylighting openings in units that will focus on the quality of lighting in one of the high-rise building units. By understanding the problem of utilizing daylighting in a room, it is expected to produce a basic planning and design in a high-rise building that is optimal in the utilization of daylighting in a condominium as one of the high rise buildings in an architectural